Dissemination of blaNDM-5 and mcr-8.1 in carbapenem-resistant Klebsiella pneumoniae and Klebsiella quasipneumoniae in an animal breeding area in Eastern China - Yang, Chengxia; Han, Jingyi; Berglund, Björn; Zou, Huiyun; Gu, Congcong; Zhao, Ling; Meng, Chen; Zhang, Hui; Ma, Xianjun; Li, Xuewen (Frontiers in Microbiology, 2022)
Animal farms have become one of the most important reservoirs of carbapenem-resistant Klebsiella spp. (CRK) owing to the wide usage of veterinary antibiotics. “One Health”-studies observing animals, the environment, and humans are necessary to understand the dissemination of CRK in animal breeding areas. Based on the concept of “One-Health,” 263 samples of animal feces, wastewater, well water, and human feces from 60 livestock and poultry farms in Shandong province, China were screened for CRK. Five carbapenem-resistant Klebsiella pneumoniae (CRKP) and three carbapenem-resistant Klebsiella quasipneumoniae (CRKQ) strains were isolated from animal feces, human feces, and well water. The eight strains were characterized by antimicrobial susceptibility testing, plasmid conjugation assays, whole-genome sequencing, and bioinformatics analysis. All strains carried the carbapenemase-encoding gene blaNDM-5, which was flanked by the same core genetic structure (IS5-blaNDM-5-bleMBL-trpF-dsbD-IS26-ISKox3) and was located on highly related conjugative IncX3 plasmids. The colistin resistance gene mcr-8.1 was carried by three CRKP and located on self-transmissible IncFII(K)/IncFIA(HI1) and IncFII(pKP91)/IncFIA(HI1) plasmids. The genetic context of mcr-8.1 consisted of IS903-orf-mcr-8.1-copR-baeS-dgkA-orf-IS903 in three strains. Single nucleotide polymorphism (SNP) analysis confirmed the clonal spread of CRKP carrying-blaNDM-5 and mcr-8.1 between two human workers in the same chicken farm. Additionally, the SNP analysis showed clonal expansion of CRKP and CRKQ strains from well water in different farms, and the clonal CRKP was clonally related to isolates from animal farms and a wastewater treatment plant collected in other studies in the same province. These findings suggest that CRKP and CRKQ are capable of disseminating via horizontal gene transfer and clonal expansion and may pose a significant threat to public health unless preventative measures are taken.